Інформаційна культура та інформаційна війна - Соколовська, Тетяна (Видавництво Львівської політехніки, 2014)
The notion of "information outlook" as a part of human information culture. The necessity of the course of lectures on the philosophy of information and information culture to create users the ability to shape their information environment for the effective and safe use of information to human adaptation to modern conditions of the society, decision-making and organization of knowledge for successful learning.
Keywords: інформаційна культура; інформаційний світогляд; інформаційне суспільство; інформаційне навчання; інформаційна безпека